Analysis And Enhancement Of The Senior High School Physical Education And Health Curriculum (Journal of Namibian Studies : History Politics Culture, 2022)
This investigation embarks on a thorough examination of the Senior High School Physical Education and Health Curriculum, aiming to dissect its existing framework, pinpoint areas for refinement, and ultimately amplify the curriculum's influence on students' physical well-being and educational journey. This scholarly inquiry seeks to evaluate and refine the Senior High School Physical Education and Health Curriculum under the purview of the Department of Education (DepEd) SHS. Its core objective lies in appraising the present condition of the curriculum, with a focus on alignment, efficacy, pedagogical approaches, challenges, and avenues for enhancement. Through a comprehensive inquiry, this study strives to address pivotal inquiries concerning the curriculum's blueprint, encompassing facets like Physical Fitness, Sports, Dance, and Recreation. Moreover, the research delves into potential disparities in curriculum status based on demographic attributes such as Age, Gender, Educational Qualification, Length of Service, and Teaching Grade Level. Employing a blended methodology, the study integrates quantitative techniques. Data collection transpires via surveys administered to 54 educators, including Physical Education and Health teachers, coordinators, and instructors from both public and private educational institutions within the Zamboanga region. The demographic insights gleaned from participants illuminate aspects of gender distribution, grade-level assignments, institutional categorization, age cohorts, tenure, and educational attainments. Rigorous validation and reliability assessments are upheld through expert scrutiny and preliminary testing of the survey instrument. Ethical considerations take precedence, safeguarding participant well-being, privacy, and informed consent. The study's findings hold the promise of advancing comprehension of the curriculum's current status and facilitating the development of strategies for its enrichment, thereby ultimately fostering heightened student engagement and enriching learning outcomes in the realms of physical education and health.